Electrochemical reaction and dissociation of glycerol on PdAu surface catalyst - Nabila A. Karim,; Norilhamiah Yahya,; Muhammad Syafiq,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Direct Glycerol Fuel Cell is one of the alternative energy that can produce electricity without burning. The production of electricity without combustion can reduce the use of fossil fuel as well as reduce environmental pollution. A new catalyst of PdAu has been synthesized in this study to increase the activity of the glycerol oxidation reaction. Morphologies analysis was performed on CNF-supported synthesized PdAu. FESEM and TEM image show the PdAu supported on the CNF surface. Both PdAu and CNF has a diameter size of 4-6 nm and 80-130 nm, respectively. In CV analysis, PdAu/CNF has produced an oxidation peak and current density at -0.9 V vs. SCE and 70 mA/cm2 , respectively. Each mechanism of glycerol dissociation step during glycerol oxidation, different atomic active sites are required in PdAu. For example, for glycerol adsorption, Au atom as an active site while for *C3 H7 O3 requires Pd atom and Au atom as the active site. The Au catalyst model shows better adsorption as Au/CNF has a slightly more negative oxidation peak than PdAu. Nevertheless, the Au catalyst showed less durability compared to PdAu.